Handelt God in de kinderdoop?: Een intercultureel perspectief op de kinderdoop als sacrament in de gereformeerde traditie - Colijn, Jos (Kerk en theologie, 2025)
The central question guiding my research is: How is Reformed theology and the practice of infant baptism appropriated by Reformed believers in different contexts? This article begins with an introduction to this topic and shortly describes the qualitative research conducted among Reformed professional theologians and ordinary believers in North India, Malawi, and the Netherlands. The article then narrows its focus to a specific question: Does God act in infant baptism? In other words, is infant baptism primarily a divine promise—a sign and seal given by God to parents and their children—or is it more akin to a ‘wet child dedication’, where the faith and decision of the parents play a constitutive role? Subsequently, I examine how ordinary believers in the research contexts reported experiencing an intensified sense of God’s presence in relation to infant baptism. Finally, I compare these empirical findings with John Calvin’s theology of baptism and insights from some key Reformed confessions. The article concludes with a summary of findings and proposes questions for further research.